Efeito do extrato de levedura sobre o desempenho produtivo e qualidade dos ovos de poedeiras - Nunes, Juliana Klug (2000)
This study aimed to evaluate the effect of graded levels (0, 1, 2 and 3%) of dietary inclusion of an yeast-extract product2 on internal and external quality of eggs and on performance of layers. A total of 240-Hy Line W36 layers (47 to 75 weeks of age) were allocated in 60 cages (4 birds per cage), divided into 15 cages per treatment. Feed intake, body weight, egg production, egg weight, egg mass, feed conversion (per dozen), feed conversion (per mass), specific gravity, eggshell weight and thickness, albumen height, Haugh units and yolk and albumen weights were evaluated. Data were subjected to ANOVA and polynomial regression. A P<0.05 was required for statements of significance. Results indicated that addition of 1,5% NuPro® resulted in better eggshell quality. The remaining variables were not statistically influenced by dietary treatments.